Geología de los cuadrángulos de: Las Playas 9-c, La Tina 9-d, Las Lomas 10-c, Ayabaca 10-d, San Antonio 10-e, Chulucanas 11-c, Morropón 11-d, Huancabamba 11-e, Olmos 12-d, Pomahuanca 12-e - [Boletín A 39] - Reyes Rivera, Luis (1987)
85 p.